New CAD modeling approach in Geant4 with half-space CSG - Qiu, Y. (Frontiers in Nuclear Engineering, 2024)
for modeling detector geometries, while representing intricate Computer Aided Design (CAD) structures can be cumbersome. This paper presents a novel approach that overcomes this limitation. A new CSG solid type called "half-space solid" has been developed, enabling the equivalent representation of complex CAD solids within Geant4. An automatic program utilizes optimized decomposition algorithms to convert CAD solids into half-space solids. The Geometry Description Markup Language (GDML) has been extended to accommodate the half-space solid type, alongside the development of interfaces for exporting converted geometries and their subsequent import into Geant4. These advancements establish a fully automated workflow for converting CAD geometries into CSG-based representations suitable for Geant4 simulations. The reliability of the half-space solid-based modeling approach has been verified through comparisons with established Geant4 solids for both simple shapes and a complex fusion reactor model. The excellent agreement obtained from these comparisons demonstrates the efficiency of this new approach.